Is manual palpation of the uterine scar following vaginal birth after cesarean section (VBAC) helpful?. (May 2015) - Dinglas, C.; Rafael, T. J.; Vintzileos, A.
Abstract Risk of uterine rupture with trial of labor after cesarean (TOLAC) is less than one percent. Discovery of uterine rupture often occurs during labor. In our case, the uterine scar is discovered to be ruptured during the postpartum period. The exact cause and time of uterine rupture is difficult to ascertain in this case, yet manual palpation of the uterine scar did not aid in the eventual diagnosis.